ZANU PF and the Government of National Unity 2009-2012 - Mazarire, Gerald C. (Weaver Press, 2016)
Historian Gerald Mazarire gives us a helpful contemporary history of the splits both in the MDC and ZANU-PF that many people outside of Zimbabwe may not fully understand. He starts by providing a summary of the somewhat questionable MDC and ZANU-PF versions of the story. Based on Prime Minister Morgan Tsvangirai’s own account of it in his autobiography, Mazarire suggests that then South African President Thabo Mbeki, along with “the support of some Western embassies in Harare”, had been involved in splitting the MDC in favour of Welshman Ncube’s faction and ZANU-PF in favor of Emmerson Mnangagwa. This strategy ultimately failed in 2004 but it did lead to major conflicts in both parties. Mazarire explains that Mbeki returned to intervene in Zimbabwean politics during the violent crisis of 2008, and the resulting Unity Accord was “hurriedly concluded” by Mbeki so that he could “attend to a crisis at home that led, in September 2008, to his own ouster from the leadership of the ANC and the South African presidency.”